REVITALISASI FUNGSI PRODUKTIF MASJID AL- MUTTAQIN DUSUN SANGGRAHAN AMPELGADING TIRTOYUDO - Hanif Maulaniam Sholah (Universitas Bina Taruna Gorontalo, 2024)
This service is a participatory action research service where the service team mingles for 2 months with the community living there to analyze what the community needs and we together try to solve it through a focus group discussion strategy. So communication is the main tool in implementing programs because our job is not to improve development but to build civilization. We form successor cadres who will continue the programs that we have agreed together with the stakeholders. This service was carried out by lecturers and students of Al-Qolam University Malang in the frame of the Real Work Lecture / KKN Program in the village of Sanggrahan Ampelgading Tirtoyudo district Malang Regency. The purpose of this service is to optimize the role of the Mosque in the benefit of the community in the social and religious fields. The mosque not only plays a role as a place of worship but also plays a role in alleviating various dynamics of problems in society because the mosque is considered a neutral and sacred place so it is needed to be a reference place for musyawaroh together with various parties. The mosque as a religious place will certainly be able to reduce turmoil and potential conflict when it is utilized to improve the character and faith of the community.